Evaluating the Acceptability and Validity of Assessing Pain and Posttraumatic Stress Symptoms in an Adaptable eHealth System for School-Age Children - Kassam-Adams, Nancy (Clin Pract Pediatr Psychol, 2019)
OBJECTIVE: To provide initial evaluation of the acceptability of a new eHealth system incorporating personalized self-report assessment of multiple health domains in school age children, and assess convergent validity of two brief measures presented via this system. METHODS: Ill or injured children (N=167) age 6 to 14 recruited in two pediatric health care systems used the prototype eScreen interface on a mobile device to select an avatar and complete brief assessments of pain and posttraumatic stress symptoms (PTSS). Children rated technology acceptability and completed validated measures for pain and PTSS. RESULTS: Children’s ratings indicated they found the eScreen interface easy to use (mean rating 4.4 on a 1–5 scale), potentially useful in helping them recover (mean=3.7), and would use / recommend it (mean=4.0). Among children age 6 to 8, mean ratings were: easy to use (3.7), usefulness (3.3), would use/recommend (3.4). Acceptability was largely consistent across child gender, family income, or usual access to mobile devices. eScreen measures showed strong convergent validity with established measures. The eScreen Pain Screener was highly correlated (r =.86 - .92) with, and evidenced strong agreement with, two validated pain measures. eScreen PTSS scores were strongly correlated with a validated PTSS measure (r=.67); a positive PTSS screen was associated with significantly higher PTSS severity. CONCLUSIONS: Study results support the acceptability (ease of use, intention to use/recommend, perceived usefulness) of these tools for older school age children, and provide strong initial evidence for the validity of two brief measures presented in a novel digital modality.